The wrath of Mulgarath - DiTerlizzi, Tony.; Black, Holly (New York : Simon & Schuster Books for Young Readers, 2004)
The Grace children, Jared, Simon, and Mallory, square off against an evil ogre who has kidnapped their mother. They enlist help of a brownie, hobgoblin and more in their quest to reunite their family.
Sequel to: The ironwood tree.
Horn Book
6.1
3-6
Keywords: Brothers and sisters -- Juvenile fiction; Single-parent families -- Juvenile fiction; Ghouls and ogres -- Juvenile fiction; Goblins -- Juvenile fiction; Brothers and sisters -- Fiction; Single-parent families -- Fiction; Goblins -- Fiction; Ghouls and ogres -- Fiction; Fantasy; Siblings -- Fiction; Single-parent families -- Fiction; Goblins -- Fiction; Ghouls and ogres -- Fiction; Fantasy fiction; Fantasy fiction